The Sion revelation the truth about the guardians of Christs's sacred bloodline - Picknett, Lynn; Prince, Clive (Touchstone, a trademark of Simon & Schuster, Inc., 2006)
Explores the mysterious Priory of Sion organization, investigating key questions about the alleged descendants of Jesus and Mary Magdalene, Leonardo da Vinci's possible membership, and the identity of Grand Master Pierre Plantard.